2016
DOI: 10.1161/jaha.115.002587
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Use of Single Antiplatelet Therapy With Edoxaban or Warfarin in Patients With Atrial Fibrillation: Analysis From the ENGAGE AF‐TIMI48 Trial

Abstract: BackgroundWe studied the concomitant use of single antiplatelet therapy (SAPT) on the efficacy and safety of the anti‐Xa agent edoxaban in patients with atrial fibrillation (AF).Methods and Results ENGAGE AF‐TIMI 48 was a randomized trial that compared 2 dose regimens of edoxaban with warfarin. We studied both the approved high‐dose edoxaban regimen (HDER; 60 mg daily reduced by one half in patients with anticipated increased drug exposure), as well as a lower‐dose edoxaban regimen (LDER; 30 mg daily, also red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 29 publications
2
64
0
2
Order By: Relevance
“…The use of antiplatelet therapy in combination with oral anticoagulation in AF patients is not uncommon in both real‐world registries and randomized trials, ranging from 24% to 37%. However, in the present study we found that only a small percentage (6.1%) of NVAF patients who initiate NOAC continued with antiplatelet therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The use of antiplatelet therapy in combination with oral anticoagulation in AF patients is not uncommon in both real‐world registries and randomized trials, ranging from 24% to 37%. However, in the present study we found that only a small percentage (6.1%) of NVAF patients who initiate NOAC continued with antiplatelet therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al [42] showed that simultaneous use of warfarin and amiodarone was not associated with adverse events in chronic OAC therapy. Also, a previous study [43] found that the combination of single antiplatelet therapy with an anticoagulant was associated with a significantly greater risk of bleeding. Sconce et al [44] showed that simvastatin reduced the mean warfarin dose in patients on chronic OAC therapy, whereas the statin effect on bleeding risk in patients on VKA is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Her risk should be managed at the time of catheterization; bleeding may be reduced with a radial artery approach (versus femoral) and careful medical management (eg, dose and selection of glycoprotein IIb/IIIa and/or P2Y 12 inhibitors [ie, clopidogrel vs prasugrel or ticagrelor]); stent selection (bare metal vs drug eluting vs newer-generation drug eluting) could influence the intensity and duration of concomitant antiplatelet therapy; and her aspirin dose should be reduced (81 mg). 53 There is mounting evidence that aspirin may not be needed at all in this scenario, and it does increase the risk of bleeding 19,[54][55][56] ; however, any discussion around aspirin discontinuation should involve the cardiac interventionalist. In addition, a proton pump inhibitor may be reasonable to reduce her risk of GI bleeding.…”
Section: Comments About Patientmentioning
confidence: 99%